Narrativas de professoras da educação infantil sobre educação para as relações étnico-raciais nas escolas Waldorf/Steiner no Brasil - Daniele Laurinda Caetano (2023)
The Early Childhood Education is the first stage of Basic Education and aims at the comprehensive development of the child in its physical, psychological, intellectual, and social aspects. In this perspective, understanding the urgency of addressing Afro-Indigenous issues in the Brazilian school context, as envisaged by Laws No. 10.639/03 and 11.645/08, the motivation for this research arose precisely from the fact that private schools in general and Waldorf/Steiner schools, in particular, exhibit a pedagogical autonomy that diverges from the specificities of these laws, as well as the BNCC itself. Consequently, the decontextualized teaching concerning the historical, cultural, and social reality of Brazil presents a noticeable imbalance, despite the vast racial/ethnic plurality in the country, perpetuating the continuity of structural racism. On the other hand, this teaching offers innovative artistic resources and elements that, by effectively engaging with the legislation, can inspire the development of new pedagogical practices. Thus, this work aimed to investigate, through the narratives of Early Childhood Education teachers from Waldorf/Steiner schools, pedagogical practices focused on Ethnic-Racial Relations Education (Erer), as well as the implementation of Law No. 10.639/03, which establishes the teaching of African and Afro-Brazilian History and Culture. The focus of this work is on issues related to black identity in the Early Childhood Education. To achieve this, the research approach was qualitative: we resorted to documentary analysis and the application of semi-structured interviews with teachers of this pedagogy to substantiate data collection. Therefore, the theoretical framework relies on legal documents regarding the objectives and organization of pedagogy in Early Childhood Education, such as the BNCC (Brazil, 2018), DCNEI, RCNEI, as well as studies on Erer (Brazil, 2004a, 2006; Gonçalves and Silva, 2018; Souza; Crosso, 2007). We addressed studies on racial prejudice and discrimination (Kilomba, 2019; Fanon, 2020), the universe of Early Childhood Education and Erer (Cardoso, 2021; Bento, 2002; Dias, 1997, 2007; Cavalleiro, 1999, 2010; Gomes, 2002, 2005, 2008, 2011, 2017, 2020, 2023; Oliveira, 2004; Oliveira, Abramowicz, 2010; Santana, 2010; Trindade, 2013), and the concept of children and childhood (Almeida, 2012; Nunes; Carvalho, 2008; Sarmento; Pinto, 1997; Gouvea, 2011; Araújo; Gomes, 2023). Additionally, we supplemented this approach with a study on Waldorf Pedagogy in Brazil - Lanz (1998); Lemonje (2016, 2022); Levi; Seidl (2023); Levy (2014, 2019); Oliveira (2020); Pinto (2009) and Castro (2016) - in addition to Waldorf Pedagogy in other contexts – Boland (2016, 2017); Boland and Muñoz (2021); Perra; Feytit (2020) and Munhoz Júnior (2021). The theoretical-methodological material developed from these analyses allows us to weave reflections and guidance that can favor the work with Erer by Critical Waldorf Pedagogy in Early Childhood Education through a decolonizing and anti-racist perspective.